EFEKTIVITAS MEDIA ONLINE SEBAGAI MEDIA PROMOSI SARUNG SUTRA MANDAR DI KABUPATEN POLEWALI MANDAR - s, asmawati (STKIP PGRI Sumatera Barat, 2020)
The purpose of this study was to determine the effectiveness of online media on the promotional aspects of mandar silk sarongs in Polewali Mandar district. The type of research used in this research is descriptive research with a quantative approach, which aims to describe the effectiveness of online media in promoting silk sarongs in Polewali Mandar Regency. The research sample was 30 respondents who were determined by proportional random sampling technique. The instrument used was a questionnaire. Data were analyzed using descriptive analysis with the AISAS model concept approach. The results of the descriptive analysis will show that the stages of the AISAS model are in the high category so that the use of online media as a promotional medium for mandar silk sarongs makes it easier for consumers to find information anywhere and anytime, compared to promotions through cultural exhibitions or festivals, television and print media that need it. quite a lot of costs and limited marketing